Pigmented Gallstone in Children With Thalassemia Syndrome - Sustiyanto, Nenny SM Sumadiono (Universitas Gadjah Mada, 2007)
Background: Pigmented gall stones in children frequently occur in spherocytosis and sickle cell anemia. The most common congenital hemolytic anemia in Indonesia is thalassemia. There is only a few studies concerning pigmented gall stones in thalassemia in the world and none in Indonesia. This study was aimed to know the prevalence of pigmented gall stones in patients with thalassemia in Pediatric Department of Dr. Sardjito Hospital.Materials and method: All patients with major thalassemia visiting Dr. Sardjito Hospital who consented to take part in the study underwent ultrasonography to identify the stone or sludge. As controls, children with no jaundice were examined.Results. There was 8,57% gallstone in thallasemia group and none in the control group.Conclusion: The occurrence of pigment gallstone in the thalassemia syndrome children in Yogyakarta the same as in other places. The risk factors of pigment gallstone should be investigated.Key words: gall stone - prevalence - thalassemia syndrome - ultrasonography.